PANI encapsulated α-MnO2 nanocomposites as photocatalytic, antibacterial and anticorrosive agents: Sustainable experimental and theoretical studies - Harish Kumar; Manisha Luthra; Manisha Punia; Ankita Yadav; Rajni Kumari; Rahul Sharma; Aarti Tundwal; Gaman Kumar; Pawanvir Kaur (Results in Engineering, 2023)
Metal nanoparticles and conducting polymers have applications in the fields like purification, separation, adsorption, photocatalytic, antibacterial, sensors, electrical conductivity, etc. The α-MnO2 nanoparticles, and polyaniline (PANI) were synthesized by the reverse micelle and chemical oxidative techniques, respectively. An in-situ technique was used for the synthesis of α-MnO2/PANI nanocomposites (NCs). The characterization of α-MnO2 nanoparticles and NCs was carried out by XRD, TEM, FTIR, and UV–visible techniques. The experimental data was supported by a theoretical (computational) study. Corrosion inhibition, antibacterial, and photocatalytic activity of α-MnO2/PANI NCs were explored. The NCs show a maximum of 87 ± 0.1% corrosion inhibition efficiency. The NCs (100 ppm concentration) degrade 89.15 ± 1.1% of methyl orange dye after 3 h of UV exposure. The photodegradation of dye follows pseudo-first order kinetics with a rate constant of 0.0657 min−1. The mechanism of photodegradation is supported by potentiostatic photocurrent measurement, impedance spectroscopy, pH variation, and chemical oxygen demand. The antibacterial property of NCs was compared to standard Hexa disk against Gram-positive and Gram-negative bacterial strains. The NCs show 18.5 mm and 15.3 mm Zone of Inhibition (1000 ppm) for S. epidermis and E. coli, respectively. The α-MnO2/PANI NCs show very good anti-corrosive, antibacterial, and photocatalytic properties.